A practical way to prepare primer human chondrocyte culture - İşyar, Mehmet; Yılmaz, İbrahim; Şirin Yaşar, Duygu; Yalçın, Sercan; Güler, Olcay; Mahiroğulları, Mahir (Elsevier Science Bv, 2016)
Biological cartilage repair is one of themost important targets for orthopedic surgeons currently. For this purpose, it is mandatory to know how to prepare a chondrocyte culture. In this study, our purpose was to introduce a method enabling orthopedic surgeons to practice their knowledge and skills on molecular experimental setup at cellular level, based on our experiences from previous pilot studies. Thus, we believe it will encourage orthopedic surgeons.
WOS: 000385438000010
PubMed ID: 27408489
Keywords: Chondrocyte; Osteochondral Tissue; Primary Cell Culture